MECHANISMS OF STIMULATION OF AGRARIAN SCIENCE FOR THE PURPOSE OF HARMONIZING FEDERAL AND REGIONAL INNOVATION AND INVESTMENT POLICY - Marianna VASILCHENKO; Ivan SANDU; Vladimir DERUNOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Improving the competitiveness of the agro-industrial complex in the context of an imbalance in the global food market and a tough sanctions policy can be achieved by stimulating the innovation and investment activities of regional and sectoral agricultural systems. The purpose of this article is to improve approaches to the optimal distribution of investments in agriculture and to develop tools to stimulate innovation and investment activity. It has been empirically proven that in Russia the priority areas for the use of investment resources are significantly underfunded, which is a blocking factor in increasing the competitiveness and economic growth of the agricultural sector of the economy. New investment mechanisms aimed at further improvement of regional and federal investment policy have been studied. Measures to stimulate innovation and investment activity are proposed and a pool of indicators for assessing indirect effects is substantiated. A mechanism for the development of the agro-industrial complex was developed on the basis of systemic mediation with the substantiation of the functions of an innovative mediator as a link between the institutional actors of the organization. This mechanism makes it possible to increase the efficiency of institutional interaction between the stakeholders of the innovation process, ensures planning and coordination of fundamental and applied research at the federal and regional levels.